The Brain - Gray, Susan Heinrichs (Chanhassen, Minn. : Child's World, 2006)
Introduces the human brain, its structure, the kinds of cells which are found there, what types of activities are controlled by its different parts, and future areas of study into its complexity.
Includes bibliographical references (p. 30) and index.
Keywords: Brain -- Juvenile literature